Rating consumption of confectionery products by persons training amateur - Mierzwa, Grażyna; Gacka, Natalia (Medical and Biological Sciences, 2016)
Human health is not defined by the absence of diseases but as a general welfare of a person that allows life full of vigour, enthusiastic performance of daily duties, fulfilling dreams and coping with different environmental conditions. Proper lifestyle should be determined by application of the principles of proper nutrition combined with regular physical activity. The human body works better when it is subjected to daily physical activity and a proper diet. Our social norms, i.e. majority of people lead sedentary lifestyle, lead to improper expression of our genes that results in the development of chronic diseases, referred to as diseases of civilization. The aim of the study was to evaluate the consumption of confectionery by people exercising in the Fit-Max fitness centre in Bydgoszcz as well as respondents’ motivation to undertake physical activity. The study showed that those exercising in Fit-Max were characterized by high physical activity:they attend classes seven days a week on average and devote from 1 to 3 hours per day for a training session selecting different forms of activity. Their main objective is weight loss, improved muscle strength, fitness and better well-being. Respondents have a wide knowledge of the principles of nutrition; however, they do not follow them in everyday life. Only a small number of respondents use restrictive diets. Although BMI of some of the surveyed indicates overweight and obesity according to the subjective assessment, there are respondents who claim that their body build is within the norm. The respondents admit to regular and frequent consumption of confectionery products due to a number of various reasons, despite the performance of physical activity. Although most respondents did not feel remorse after consumption of sweets, they have reduced the amount of food assortment in favour of increased physical activity due to the increase in body weight.